Pengaruh Nutrisi dan Perilaku Hidup Bersih dan Sehat dalam Mencegah Cacingan Anak Sekolah - Lalangpuling, Indra Elisabet; Linda Augustien Makalew; Michael V. L Tumbol; Nurmila Sunati; Jasman (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
This community service activity aimed to increase knowledge about the transmission of worm infections and raise awareness of the importance of Clean and Healthy Living Behavior (PHBS) among students, parents, and health cadres. The activity was held at GMIM Talawaan Bantik Elementary School in collaboration with Wori Public Health Center, Wori District, North Minahasa Regency, in June 2025. It involved lecturers and students from the Medical Laboratory Technology Department of Poltekkes Kemenkes Manado, school staff, village officials, and health center representatives. The activities included health education, donations, and blood type examinations. A total of 74 participants were involved, consisting of students, parents, and health cadres. The educational session was well received, as evidenced by active participation during discussions. Donations were handed over to the school principal, and blood type tests were conducted on 56 participants, with blood type O being the most common. Conclusion : The program successfully increased participants’ knowledge of PHBS and contributed to reducing the potential incidence of intestinal worm infections in the school environment.